2019
DOI: 10.1242/jeb.203596
|View full text |Cite
|
Sign up to set email alerts
|

The distinct phenotypic signatures of dispersal and stress in an arthropod model: from physiology to life history

Abstract: Supplementary Figure 1. Effect of dispersal status and host plant on fecundity, measured as the number of eggs laid in the first 24h of Experiment 1. Dispersal effect: Χ² = 1.47, df = 1, p = 0.23 ; Host plant effect: Χ² = 43.34, df = 1, p = 4.59 × 10 -11 ; Interaction effect: Χ² = 0.00, df = 1, p = 0.95 (quasi-Poisson GLM). Supplementary Figure 2. (next pages)Observed metabolite concentrations in Experiment 2. Box and black dots: observed values, coloured dots: predicted means based on fixed and random effects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Hence, while the removed old plants may have contained mites or unhatched eggs, we chose for this refreshment procedure to maintain natural movement dynamics. It is for instance known that especially young fertilised females disperse more (Li & Margolies, 1993) and dispersive individuals may differ in their body condition or performance compared to sedentary individuals (Bonte et al, 2014; Dahirel et al, 2019). This refreshment procedure may have caused an extra competitive pressure if one species was more dispersive or delayed its dispersal for avoiding competition, but we preferred to design the experiment in a way that it resembled more the actual life strategy of spider mites (colonisation with few founders followed by rapid growth).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, while the removed old plants may have contained mites or unhatched eggs, we chose for this refreshment procedure to maintain natural movement dynamics. It is for instance known that especially young fertilised females disperse more (Li & Margolies, 1993) and dispersive individuals may differ in their body condition or performance compared to sedentary individuals (Bonte et al, 2014; Dahirel et al, 2019). This refreshment procedure may have caused an extra competitive pressure if one species was more dispersive or delayed its dispersal for avoiding competition, but we preferred to design the experiment in a way that it resembled more the actual life strategy of spider mites (colonisation with few founders followed by rapid growth).…”
Section: Methodsmentioning
confidence: 99%
“…The removed old plants may have contained mites or unhatched eggs, but we nevertheless chose this refreshment procedure to maintain relatively natural movement dynamics. It is for instance known that especially young fertilised females disperse more (Li & Margolies, 1993) and dispersive individuals may differ in their body condition or performance compared to sedentary individuals (Bonte et al, 2014;Dahirel et al, 2019). This refreshment procedure may have caused an extra competitive pressure if one species was more dispersive or delayed its dispersal for avoiding competition, but we preferred to design the experiment in a way that it resembled more the actual life strategy of spider mites (colonisation with few founders followed by rapid growth).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…This phenotypic plasticity is usually expressed in body size, morphology, physiology, and behavior (Parsons et al 2011; Koeller, Mohn, and Etter 2000; Kamioka and Iwasa 2017; Le Galliard, Paquet, and Mugabo 2015; Woodworth et al 2017). Since dispersal is performed by a non-random subset of individuals from the population that share specific life history traits (Bonte et al 2012; Clobert et al 2012; Dahirel et al 2019) and physiology (Goossens et al 2020), connectivity changes will equally affect the sorting of phenotypes, and therefore phenotypic variation ( kind structure ) among patches. The spatial organization of phenotypes among and within patches then again has the potential to affect population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…We used the two-spotted spider mite Tetranychus urticae as a model to demonstrate how the spatial self-organization of phenotypes (i.e., the emerging kin and kind structure) equalizes metapopulation dynamics across connectedness levels (Urban et al 2020). The prerequisites for such a phenotypic self-organization are present: phenotypic variation in relation to local densities, stage and sex structure (Dahirel et al 2019; De Roissart, Wang, and Bonte 2015), density and kin-competition related dispersal (Van Petegem et al 2018; Fronhofer, Poethke, and Dieckmann 2015). Moreover, previous studies showed that this species’ phenotype-dependent dispersal maximizes fitness (Dahirel et al 2019; Bonte et al 2014).…”
Section: Introductionmentioning
confidence: 99%